2016
DOI: 10.1186/s13049-016-0301-9
|View full text |Cite
|
Sign up to set email alerts
|

Prehospital control of life-threatening truncal and junctional haemorrhage is the ultimate challenge in optimizing trauma care; a review of treatment options and their applicability in the civilian trauma setting

Abstract: IntroductionExsanguination following trauma is potentially preventable. Extremity tourniquets have been successfully implemented in military and civilian prehospital care. Prehospital control of bleeding from the torso and junctional area’s remains challenging but offers a great potential to improve survival rates. This review aims to provide an overview of potential treatment options in both clinical as preclinical state of research on truncal and junctional bleeding. Since many options have been developed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
66
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(73 citation statements)
references
References 137 publications
(164 reference statements)
0
66
0
3
Order By: Relevance
“…It is notable that although haemostatic agents have been recommended for use in areas where tourniquets cannot be used (such as junctional zones and the trunk),2 we found that there were a large number of applications to the extremities. This is likely due to the predominance of extremity trauma in recent conflicts,1 and the presence of coagulopathy that might hinder the cessation of bleeding.…”
Section: Discussionmentioning
confidence: 77%
“…It is notable that although haemostatic agents have been recommended for use in areas where tourniquets cannot be used (such as junctional zones and the trunk),2 we found that there were a large number of applications to the extremities. This is likely due to the predominance of extremity trauma in recent conflicts,1 and the presence of coagulopathy that might hinder the cessation of bleeding.…”
Section: Discussionmentioning
confidence: 77%
“…Current standard procedure for the treatment of catastrophic abdominal haemorrhage is to immediately evacuate to allow rapid surgical intervention [45]. Massive transfusion protocol is sometimes used, but often achieving this sort of haemorrhage control early on is difficult due to circumstances such as on-going gunfire, remoteness, and skill level of care providers [46]. After referring to current protocol for the treatment of internal bleeding and haemorrhage in pre-hospital and clinical phases, it is evident that alternative treatment methods are necessary.…”
Section: Current Treatments Of Internal Bleeding and Coagulopathymentioning
confidence: 99%
“…fluid was restricted . Instead, the emphasis should be on timely transport to an appropriate hospital for surgical intervention …”
Section: Introductionmentioning
confidence: 99%
“…fluid to elevate blood pressure in these patients runs the risk of increased bleeding, hypothermia, anaemia and coagulopathy. [6][7][8] Data from one large, randomised, controlled trial suggested improved outcomes in penetrating truncal trauma if i.v. fluid was restricted.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation